Non-invasive brain stimulation in Parkinson disease rehabilitation - Minakshi Gupta (Romanian Neurosurgery, 2021)
Patients diagnosed with Parkinson’s disease suffer from various symptoms affecting motor and non-motor functions having adverse effects on their quality of life. Hence various evolving treatment methods are employed and researched for further benefits apart from the conventional pharmacological, surgical and rehabilitative treatment adjuncts. In this review article, we have summarized the therapeutic effects of noninvasive brain stimulation on various symptoms in Parkinson disease as it is the recent emerging tool and various researchers are working on application of this technique in Parkinson disease. It has been found that both transcranial direct current, as well as transcranial magnetic stimulation, is able to produce considerable effects in Parkinson patient.